Development of Insulation Panel from Recycled Denim Jeans for Thermal and Acoustic Properties - BINTI KAMAL, EZANI FIZAFARISHA; Mohd Fahmi Abdul Rahman, (Progress in Engineering Application and Technology, 2025)
Develop an insulation panel made from recycled textile have been famous and many research have investigate the performance for thermal and acoustic performance. The aim of this research is to to identify optimum proportions of recycled denim jeans for acoustic and thermal performance, conduct sound absorption testing using sound reduction index and thermal conductivity testing for thermal performance, and compare the result with previous study on recycled denim jeans based on materials. Testing conducted using SOLTEQ model HE110 for thermal conductivity, while Sound Reduction Index experiment is used to measure sound absorption coefficients. From the analysis, jeans panels have the highest density than paper panel and cotton panel making jeans panel was the highest density among other recycled textile panel. From the testing, the thermal conductivity of S2 has the highest with 0.129 W/m⁰C than other two proportions shows that S2 is a weak thermal resistance, while S1 is a good thermal resistance with 0.083 W/m⁰C. The lowest recorded value of sound absorption is 38.16dB from recycled paper panel and the higher is S3 jeans panel with 50.20dB indicates to good sound absorption or reflection. Jeans panels S3 is the better choices for insulation panel as it absorb more sound and high thermal resistance. Sound reduction can increase acoustic comfort in building, while low thermal conductivity can make the building are comfortable to live in.